Laser Beam‐Induced Transient Acoustic Waves in Graphene Oxides. Issue 4 (29th December 2020) - Thekkekara, Litty V.; Cole, Ivan
Abstract : Laser beam‐induced graphene oxides (GOs) with excellent tunable properties have to find attention in various applications. But, the understanding of the complex mechanics involved in this reduction process is incomplete, most primarily the reduction using ultrashort laser beam pulses. Herein, the influence of laser beam‐induced acoustic waves on the photoreduction as well as the generation of a reversible phase in the GOs using photoacoustic studies is presented. However, these waves influence the phase transition in GOs. These observations find aspiring applications for next‐generation optical technologies, such as data storage and neural chips. Abstract : The influence of laser beam‐induced acoustic waves in the photoreduction as well as the generation of a reversible phase in the graphene oxides using photoacoustic studies is presented.